The prioritisation of motivationally salient stimuli in hemi-spatial neglect may be underpinned by goal-relevance: A meta-analytic review. (May 2022) - Brown, Chris R.H.
Abstract: Damage to regions underpinning attention can result in hemi-spatial neglect, characterised by inattention to stimuli presented in contralesional space. Motivationally salient stimuli (e.g. reward/threat) are, however, resilient to neglect and more likely to be detected compared to neutral stimuli. Prominent theories of attention suggest that the motivational detection advantage in neglect is underpinned by a goal-independent 'emotional attention' system. However, measures of stimulus awareness previously used often present the stimuli as part of the goal-relevant target set. Previous findings may therefore be more consistent with top-down attentional selection, which is preserved in some cases of neglect. Using multilevel and Bayesian meta-analytic approaches to individual case and group data, the evidence for a motivational detection advantage in neglect, and conditions when it emerges, were examined and conceptual claims reviewed. Cumulative evidence suggested that in perceptually simple conditions, when a single stimulus appeared, there was no evidence of a motivational detection advantage (Individual: k  = 36; log OR  = .02, 95%CI [-.44, .47]; Group: k  = 2, d z  = .24, 95%CI [-.26, .74]). Conversely, under more perceptually demanding conditions, with multiple goal-relevant stimuli, motivationally salient stimuli were detected more than neutral stimuli in the contralesion side of space (Individual: k  = 37, log OR  = 1.04, 95%CI [.74, 1.34]; Group: k  = 7, d z  = .81, 95%CI [.27, 1.35]). Across investigations the detection advantage occurred when the motivationally salient stimulus was a target, and under perceptually demanding conditions when goal-irrelevant motivationally salient stimuli are usually suppressed. The current evidence therefore does not strongly support a goal-independent mechanism, and a top-down account remains plausible. This account can be contextualised within existing models of neglect, whereby perceptual load induces suppression of contralesional space when ipsilesional space is prioritised. Target stimuli may, however, still be detected under reduced perceptual capacity due to their goal-relevance, which may be selectively enhanced by motivational salience.